PENILAIAN KESEHATAN BANK SYARIAH MENGGUNAKAN METODE REGC - zalina, indah (Institut Agama Islam Tafaqquh Fiddin Dumai, 2024)
Sharia bank health assessment is an important evaluation process in determining the performance and financial stability of sharia-based banks. This assessment covers a number of factors, including compliance with sharia rules and principles, financial performance, risk management, and compliance with regulations. The aim of carrying out this bank health assessment is to ensure that sharia banks can maintain their stability, provide quality services to customers, and comply with ethical standards and Islamic law. The research method used is a qualitative approach with library research. The health of the bank can be concluded that the bank can carry out its operations well, so that it is able to guarantee the continuity of the bank's financial and business operations so that public confidence remains in channeling its funds. To determine the health level of a bank, it can be done through six assessment methods, namely CAMELS. However, starting from January 1 2012, the RGEC method is used to assess the bank's health level in the last period up to December 31 2011, and simultaneously revoke Bank Indonesia Regulation No.6/ 10/PBI/2004 concerning the Health Level Assessment System for Commercial Banks using the CAMELS method.